Application of syntrophic co-culture Chlorella sorokiniana and Streptomyces thermocarboxydus in semi-continuous system for cassava wastewater treatment and biomass production - Mohamad Padri; Nittaya Boontian; Maisarah Munirah Latief; Misdar Amdah; Mohamed Sahrul Tamzil (Green Technologies and Sustainability)
Application of microalgae and mutualistic symbionts have been widely developed for wastewater treatment and algal biomass production. This study aimed to examine and compare the application of single and co-culture of alga Chlorella sorokiniana P21 with Streptomyces thermocarboxydus BMI in semi-continuous system to treat biogas effluent wastewater and generate algal biomass. A sequence of batch and semi-continuous system was applied to assess the single and co-culture nutrients removal (N, P, and COD) along with the biomass productivity for sterilized and raw (unsterilized) wastewater. Different Hydraulic Retention Times (HRTs) were applied to the system, and it was found that 5 days HRT resulted the highest nutrients removals in single and co-culture conditions. Nevertheless, this HRT was also in line with the predicted optimum HRT based on the growth rate in the batch conditions. However, low HRTs were found not to allow the algae to increase the pH and DO in the culture. This result exhibits the massive potencies of microalgae-bacterial co-culture to apply on wastewater treatment in larger scale with reliable removal and biomass production.